Effect of Geographical Environment on Success Rate of Rukyat Hilal at Observatorium CASA Assalam - Machzumy . (University of Muhammadiyah Sumatera Utara, 2019)
Rukyat hilal at the beginning of the month of Qamariah, especially the beginning of Ramadan, and Shawwal is a study of celestial spells which often attract attention because of the frequent differences. This dilator is behind the uncertainty of the rukyat results due to the lack of observable rukyat results. This is partly due to the location of the rukyat which is not yet safe enough from various natural disturbances, such as the geographical environment of the observatory. CASA Assalam Observatory is one of the locations designated by the government as a place to report rukyat results. CASA Assalam Observatory located in the middle of Surakarta city, with a height of 144 mdpl, and is 69 km from the sea. But from 5 years of observation of the new moon, only one time succeeded in destroying the hilal. The research method uses descriptive analytical methods, collecting data by means of documentation and direct observation. The results of this study found that one of the causes of the low success rate of rukyatul hilal in the observatory was because the observatory environment located in urban areas was disturbed by the number of buildings, air pollution and light pollution.